DIRECTIONS OF THE STATE POLICY OF HEALTHCARE REFORM IN UKRAINE - O. Kravchenko, Sergii; V. Shpachuk, Vitaliy (Revista Gênero e Interdisciplinaridade, 2021)
Today in Ukraine, the theme of health care is extremely relevant and painful for most Ukrainian society. The Ukrainian healthcare system has a low level of financial and material security, a technically backward infrastructure, imperfect management, requires significant financial investments, and the use of innovative management and medical technologies that the state cannot provide due to the crisis and limited budget. Therefore, the topic of health care is one of the most discussed in society, because health care concerns everyone without exception, a citizen of our state, which is why the process of formation and implementation of state policy in the field of health today is almost the most important issue in Ukraine. In view of this, the article analyzes the state of the healthcare system of Ukraine, the current state policy of Ukraine in the field of health care. The features and drawbacks of the modern healthcare system of Ukraine, the difficulties faced by the state in the process of reforming the healthcare system are highlighted. The necessity of changing the existing healthcare system as a prerequisite for the following changes in this area, the preconditions of European integration development of Ukraine, achievement of modern health standards, based on the current realities of Ukraine's existence, national interests, ongoing system changes in Ukraine, as well as needs state and society. The directions of the state policy of healthcare reform in Ukraine have been determined, and it has been proved that the reform of the medical sphere requires significant changes in the socio-political, financial-economic, administrative-territorial, legal and other spheres of state activity.